Analisis Perhitungan Estimasi Biaya pada Rumah Tinggal 2 Lantai Menggunakan Material Kontainer - Yoga, Alwan Adhirajasa (Civil Infrastructure Engineering and Architectural Design, 2023)
The dwindling availability of land has resulted in an increase in the price of residential houses every year, moreover cities with relatively denser populations have an increase in house prices of more than 20% each year. The design of residential houses by utilizing used containers will save material, transportation, and construction costs, so it is hoped that this alternative can be developed to become a sustainable solution. The research was conducted by designing a 2-storey container house with a building area of 172.8 m2 using the SketchUp2022 software and then calculating the estimation cost analysis. The results of the estimation costs show that conatainer house needs cost of IDR 565,476,007.90 or IDR 2,827,380.04/m2 included tax. So that container house can savings of 19.22% - 43.45% when compared to the average price of conventional houses in Indonesia of IDR 4,500,000.00 - IDR 6,000,000.00 per m2 .